Comparing the Use of Visual Analogue Scales and Likert-type Scales in International Agricultural and Extension Education Surveys - Keegan D. Gay; Arthur Leal; Taylor K. Ruth; Alexa J. Lamm; Joy N. Rumble (Journal of International Agricultural and Extension Education, 2015)
Data collected using survey methodology is readily used to provide insight into improving international agricultural and extension education programs. The evolution of survey technology has allowed educators access to a growing number of audiences; however, the escalating quantity of surveys contributes to greater survey fatigue. Utilizing multiple forms of response, such as Likert-type scales and visual analog scales, may relieve some symptoms of survey fatigue. The use of visual analog scales may allow respondents the ability to respond more freely to questions where fractional differences can hold a wealth of information. This study examined the possible advantages of utilizing visual analog scales rather than Likert-type scales in surveys. A Web-based survey was conducted with respondents randomly assigned to one of two treatments: comparison constructs in traditional Likert-type scale presentation form using radio buttons or comparison constructs with a Visual Analog Scale presentation. Results indicated responses from visual analog scales were similar to those on Likert-type scale questions. No significant additional time to complete the constructs was found; however, a significantly lower non-response rate existed for one construct using the Likert-type scale (10% compared to 32%). Seventy-five percent of the respondents given visual analog scales utilized the freedom to select increments between the restricted points of radio buttons.
Keywords: needs assessment; Visual Analog Scale; survey design; program evaluation